Penguatan Gender dalam Pengambilan Kebijakan Birokrasi di Kota Gorontalo - Walahe, Dewi (Universitas Gorontalo, 2018)
ABSTRACT The long-term objective of this research is the birth of a process of describing women's involvement in the bureaucratic decision-making process, and the model of gender strengthening in bureaucratic decision-making in Gorontalo City. The research method used is qualitative research with data collection techniques through: interviews, documentation, and FGD. Then the collected data will be analyzed by triangulation data. The results show that: first, so far the existence of women in the Gorontalo City government in the bureaucratic decision-making process is still less than optimal, although the potential quantity of women is 3,023 (66.97%) compared to 1,491 men (33.03%). The progress of the role of women in the bureaucratic leadership only 6 people occupied the heads of regional apparatus organizations and 24 others were men. This symptom certainly has an impact on demands. women must play their role in realizing democracy that is not gender biased as well as proof of the maturity of a nation. Keuda, the Gender Strengthening Model in the decision making of the bureaucracy in Gorontalo City is the zero-sum and positive-sum models.